THEORY OF SENTENCE AND PARTS - Teshaboyeva Nafisa Zubaydulla qizi; Egamberdiyeva Oyguljon (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation:This article delves into the theory behind sentence components, analyzing the primary, secondary, and tertiary elements that create sentence structures in English. The foundational elements, such as subjects, predicates, objects, and complements, are essential for constructing sentences. Principles like agreement, consistency, and parallelism play a crucial role in maintaining clarity and correctness. Secondary elements, including modifiers, phrases, and clauses, enhance meaning and add detail. Additionally, the article discusses tertiary components, like conjunctions, interjections, and transitional devices, while pointing out the difficulties they can pose in ensuring sentence coherence. By grasping these elements, individuals can improve their skills in crafting effective and grammatically accurate sentences.